Upaya Peningkatan Hasil Belajar Matematika Dengan Menerapkan Model Team Assisted Individualization - Astuti Astuti (JURNAL GLOBAL EDUKASI, 2021)
Abstrak: The purpose of this research is to improve student learning outcomes by applying the model Team assited Individualization in lieu of the conventional learning model. Classroom action research was conducted in three cycles at 132407 Tanjungbalai Elementary School. The subjects were students of class V and the object of study is the result of student learning in mathematics materials algebraic operations which include the reduction of integers, integer multiplication, and division of integers. The results showed an increase in the average value of 5.15 students in the first cycle to 9.64 in the third cycle. The percentage of students learning completeness 43.14% in the first cycle to 96.08% in the third cycle. Kata kunci: Team Assited Individualization, operasi aljabar, bilangan bulat Abstrak: Tujuan penelitian ini adalah untuk meningkatkan hasil belajar siswa dengan menerapkan model Team Assited Individualization sebagai pengganti dari model pembelajaran konvensional. Penelitian tindakan kelas dalam tiga siklus ini dilaksanakan di SD Negeri 132407 Tanjungbalai. Subjek penelitian ini adalah siswa kelas V dan objek penelitian adalah hasil belajar siswa pada pelajaran Matematika materi operasi aljabar yang meliputi pengurangan bilangan bulat, perkalian bilangan bulat, dan pembagian bilangan bulat. Hasil penelitian menunjukkan terjadi peningkatan nilai rata-rata siswa 5,15 pada siklus I menjadi 9,64 pada siklus III. Persentase ketuntasan belajar siswa 43,14% pada siklus I menjadi 96,08% pada siklus III. Kata kunci: Team Assited Individualization, operasi aljabar, bilangan bulat